Differences in EFL learners’ burnout levels and receptive language skills with regard to the mindfulness-based instruction - Moghadam Haniyeh; Ghanizadeh Afsaneh; Ghonsooly Behzad (ExELL (Explorations in English Language and Linguistics))
The main aim of education is to provide students with academic knowledge and skills. In this process, some students experience burnout, which negatively affects their productivity and effectiveness. This study experimentally examines the impact of mindfulness-based instruction on burnout and students’ achievement in receptive language skills among 64 learners of English as a foreign language (EFL) via a mixed-methods approach (QUAN→ qual) within a single framework. The techniques implemented in the experimental group, i. e. 32 participants, included observance of all experience, analyzing, planning, judging, reasoning, and fantasizing (van Vreeswijk et al., 2014). Furthermore, the techniques were inspired by Pirson et al. (2012) conceptualization that mindfulness comprises novelty producing, novelty seeking, engagement, and flexibility. The results of posttest revealed these techniques efficiently enhanced the abovementioned variables.